A educação musical no Ensino Médio: um estudo de caso no contexto do Instituto Federal do Maranhão - Trajano, Tayane da Cruz (2016)
This research seeks to understand how the music education is configured in Instituto Federal do Maranhão based on two campuses in the capital: Centro Histórico and Monte Castelo. Investigating the theoretical concepts and the legal basis for the teaching of arts/music at the Instituto Federal do Maranhão, seeks to know the pedagogical and musical concepts that direct the teaching work, analyzes the documents that constitute the musical practices in these institutions, identifying them as the projection and legitimation within the Instituto Federal do Maranhao. Based on authors who study the issue with research focused on music education problems in the country met the authors: Figueiredo (1997); Penna (2012); Fonterrada (2008); Bushman and Souza (2009); Loureiro (2003); Ahmad (2014); Esperieião (2012); those who study the relationship Music, Education and high school: Dayrell (2015); Santos (2009); Oliveira (2012); Souza (2009); Carrano and Falcao (2011), who study on pedagogical-musical concepts: Kraemer (2000); Bellochio (2014); Brito (2011); Souza (2015; 2009); Materiro (2011); Hentschke, Souza and Oliveira (1999), also specifically on the high school at the Federal Institute: Rego (2013) and Aguiar Junior (2012), still sought to research that bring related clearly to practices in the classroom, such as Del Ben (2001); Hentschke, Souza and Oliveira (1999). All this theoretical deeply led to the critical points that encouraged this research based on the importance of analyzing the legitimacy of music education in schools. Descriptive and qualitative approach this research uses the case study method. The data were recorded by observation, semi-structured interviews with the school community and the analysis of the documents that guide the music education at this institution. The results reveal that the IFMA is an institution with a clear historical apparatus and influencer in the integrated formation of the human being and therefore enables all due art / music on your academic context so that the process of legitimation of pedagogical-musical practices is evident in the two campuses studied. It also reveals that the campuses are differ by their peculiarities, which will be shown to an end through an analogy.